What is the risk of death or severe harm due to bone cement implantation syndrome among patients undergoing hip hemiarthroplasty for fractured neck of femur? A patient safety surveillance study. Issue 6 (12th June 2014) - Rutter, Paul D; Panesar, Sukhmeet S; Darzi, Ara; Donaldson, Liam J
Abstract : Objective: To estimate the risk of death or severe harm due to bone cement implantation syndrome (BCIS) among patients undergoing hip hemiarthroplasty for fractured neck of femur. Setting: Hospitals providing secondary and tertiary care throughout the National Health Service (NHS) in England and Wales. Participants: Cases reported to the National Reporting and Learning System (NRLS) in which the reporter clearly describes severe acute patient deterioration associated with cement use in hip hemiarthroplasty for fractured neck of femur (assessed independently by two reviewers). Outcome measures: Primary—number of reported deaths, cardiac arrests and periarrests per year. Secondary—timing of deterioration and outcome in relation to cement insertion. Results: Between 2005 and 2012, the NRLS received 62 reports that clearly describe death or severe harm associated with the use of cement in hip hemiarthroplasty for fractured neck of femur. There was one such incident for every 2900 hemiarthroplasties for fractured neck of femur during the period. Of the 62 reports, 41 patients died, 14 were resuscitated from cardiac arrest and 7 from periarrest. Most reports (55/62, 89%) describe acute deterioration occurring during or within a few minutes of cement insertion. The vast majority of deaths (33/41, 80%) occurred on the operating table. Conclusions: These reports provide narrative evidence from England and Wales that cement use in hip hemiarthroplasty for fractured neck of femur is associated with instances of perioperative death or severe harm consistent with BCIS. In 2009, the National Patient Safety Agency publicised this issue and encouraged the use of mitigation measures. Three-quarters of the deaths in this study have occurred since that alert, suggesting incomplete implementation or effectiveness of those mitigation measures. There is a need for stronger evidence that weighs the risks and benefits of cement in hip hemiarthroplasty for fractured neck of femur.